Stimuli-disassembling gold nanoclusters for diagnosis of early stage oral cancer by optical coherence tomography - Kim, Chang Soo; Ingato, Dominique; Wilder-Smith, Petra; Chen, Zhongping; Kwon, Young Jik (Nano convergence, 2018)
A key design consideration in developing contrast agents is obtaining distinct, multiple signal changes in diseased tissue. Plasmonic gold nanoparticles (Au NPs) have been developed as contrast agents due to their strong surface plasmon resonance (SPR). This study aims to demonstrate that stimuli-responsive plasmonic Au nanoclusters (Au NCs) can be used as a contrast agent for optical coherence tomography (OCT) in detecting early-stage cancer. Au NPs were clustered via acid-cleavable linkers to synthesize Au NCs that disassemble under mildly acidic conditions into individual Au NPs, simultaneously diminishing SPR effect (quantified by scattering intensity) and increasing Brownian motion (quantified by Doppler variance). The acid-triggered morphological and accompanying optico-physical property changes of the acid-disassembling Au NCs were confirmed by TEM, DLS, UV/Vis, and OCT. Stimuli-responsive Au NCs were applied in a hamster check pouch model carrying early-stage squamous carcinoma tissue. The tissue was visualized by OCT imaging, which showed reduced scattering intensity and increased Doppler variance in the dysplastic tissue. This study demonstrates the promise of diagnosing early-stage cancer using molecularly programmable, inorganic nanomaterial-based contrast agents that are capable of generating multiple, stimuli-triggered diagnostic signals in early-stage cancer.